2020
DOI: 10.1080/13607863.2019.1709156
|View full text |Cite
|
Sign up to set email alerts
|

Towards an active and happy retirement? Changes in leisure activity and depressive symptoms during the retirement transition

Abstract: Objectives: Retirement is a major life transition in the second half of life, and it can be associated with changes in leisure activity engagement. Although theories of retirement adjustment have emphasized the need to find meaningful activities in retirement, little is known about the nature of changes in leisure activity during the retirement transition and their association with mental health. Methods: Based on four annual waves of the 'Health, Aging and Retirement Transitions in Sweden' study, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 78 publications
2
69
2
Order By: Relevance
“…Moreover, given that older people tend to pursue intrinsically motivated goals rather than extrinsically motivated goals they may be more able to orient towards activities that may satisfy their basic psychological need of relatedness (Sheldon and Kasser 2001). Finally, as mentioned before, a previous study based on the HEARTS sample found increased engagement in social activities after retirement (Henning et al 2020). However, even if the number of social contacts should decline over retirement, this does not necessarily mean that feelings of relatedness should decline.…”
Section: Need Satisfaction Across the Retirement Transitionmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, given that older people tend to pursue intrinsically motivated goals rather than extrinsically motivated goals they may be more able to orient towards activities that may satisfy their basic psychological need of relatedness (Sheldon and Kasser 2001). Finally, as mentioned before, a previous study based on the HEARTS sample found increased engagement in social activities after retirement (Henning et al 2020). However, even if the number of social contacts should decline over retirement, this does not necessarily mean that feelings of relatedness should decline.…”
Section: Need Satisfaction Across the Retirement Transitionmentioning
confidence: 86%
“…Consequently, once the work-related experience of competence is not available anymore, many retirees are probably able to find new sources for competence in retirement (Henning et al 2019a). For example, earlier results from the HEARTS study showed that participants seem to engage more in leisure activities or voluntary work after retirement (Henning et al 2020). Leisure activity is known to fulfill the needs for competence and relatedness (Leversen et al 2012) and it has been argued that activity engagement can help to maintain perceived continuity in retirement by replacing the work role (Atchley 1976;van Ingen and Wilson 2017).…”
Section: Need Satisfaction Across the Retirement Transitionmentioning
confidence: 99%
“…Retirement was the most examined life transition with 29 studies (27.1%). In general, retirement was associated with increases in leisure-time PA, (recreational) walking, and domestic activities [40,84,85,87,88,90,91,93,96,99,100,103,104,[106][107][108][109]132] and decreases in occupational PA, active transportation, and total PA [83,84,93,103,104,106,107]. With regard to PA intensities, an increase especially in light and moderate PA occurred [87,96], whereas findings on vigorous and moderate-to-vigorous PA were more ambiguous [93, 95, 96, PLOS ONE 105,132].…”
Section: Employment-related Events and Transitionsmentioning
confidence: 93%
“…Some studies reported on the long-term trajectories of PA patterns across the retirement transition indicating that PA tends to increase right after retirement but declines later on [91,99,102,104,105]. In contrast, two studies found evidence that PA levels remained stable after an initial increase [101,108]. Findings for the pre-retirement period were ambiguous with reported increases and decreases in PA [102,105] depending on domain and gender.…”
Section: Employment-related Events and Transitionsmentioning
confidence: 99%
“…For others, it means a permanent liberation from stressful work [ 5 ]. However, for an increasing number of people, retirement occurs during a productive and satisfactory professional stage of life and is considered a personal loss [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%